APRESIASI SISWA KELAS V SEKOLAH DASAR DALAM HASIL KARYA SENI TENUN TROSO JEPARA - Idris, M. Rizal Maulana; Kironoratri, Lintang; Fajrie, Nur (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
This study aims to determine the appreciation process and describe the results of the appreciation of fifth grade students in the work of Troso woven art at SDN Demangan Jepara.The research method used is qualitative narrative. Data sources were obtained directly through observation and interviews with all fifth grade students. This research was conducted in July 2024 at SDN Demangan Jepara. Data validation in this study used triangulation of data sources. The data analysis technique used refers to the Miles Huberman model with a flow of data reduction, data presentation, and conclusions/verification.The results of this study indicate that fifth grade students at SDN Demangan Jepara have high potential in appreciating torso woven art. This research can be a source of learning for students in learning fine arts through project-based learning by creating two or three-dimensional works of art inspired by troso woven motifs, field visits that allow them to study the form and aesthetics of troso weaving directly by observing the weaving process, interacting with craftsmen to gain deeper knowledge.